(untitled) - Miller, Mark (Hoboken, N.J, 2004)
Includes many practical case studies as further illustration of the concepts discussed.
Keywords: Computer networks,TCP/IP (Computer network protocol),Network performance (Telecommunication),Internet,Mạng máy tính,TCP/IP (giao thức mạng máy tính),Hiệu suất mạng (Viễn thông),Mạng máy tính; Management,Quản lý